Biomedical porous Ti-16Nb-10Zr-(0-15)Ta alloys - GÜLSOY, HAMİT ÖZKAN (CARL HANSER VERLAG, 2019)
To improve the properties of compact Ti alloys for biomedical applications, porous Ti-16Nb-10Zr-(0-15)Ta (wt.%) alloys were produced by the space-holding method using an ammonium hydrogen carbonate space holder. The pore size distribution, porosity ratio and mechanical properties of the obtained porous alloys were investigated. Also, the effect of Ta addition on the microstructure and mechanical properties was investigated. It has been determined that the sintered porous Ti-Nb-Zr-Ta alloys have suitable mechanical properties (elastic modulus: 36.32-38 GPa, transverse rupture strength: 154-281 MPa) for hard tissue implants.
Keywords: Porous Ti-Nb-Zr-Ta alloys; Space holder method; Elastic modulus; Implant; TI-TA ALLOYS; MECHANICAL-PROPERTIES; MICROSTRUCTURE; MORPHOLOGY; BEHAVIOR